Research progress in field synergy theory and its application in heat transfer processes of non-Newtonian fluids - HUANG Shi-zheng1, PAN Wei1, YANG Wei-min2, ZENG Xian-kui1, JIAN Ran-ran1,2,3 (Hecheng xiangjiao gongye)
"The process of development and improvement of field synergy principle were summarized, the exploration of the application of field synergistic principle to enhance heat transfer in non-Newtonian fluids, such as power-law fluids and polymer processing and the difficulties that needed to be overcome were systematically summarized and analyzed with 43 references, and the development prospects of field synergistic principle in optimizing the heat transfer process of polymer melts and achieving high-quality and high-efficiency plasticization were also prospected. "